A high energy storage lead-free relaxor ferroelectric thick film ceramic and its preparation method and application

By multi-ion doping in relaxed ferroelectric thick film ceramics and using wide bandgap oxides, combined with casting method, the ceramic thickness is solved, and the existing lead-free antiferroelectric ceramics have been achieved in terms of energy storage efficiency and frequency stability, and ceramic materials with high energy storage efficiency and frequency stability are achieved, suitable for high-power pulsed devices.

CN118307319BActive Publication Date: 2025-03-07GUANGDONG UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410301016.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-15
Publication Date
2025-03-07
Estimated Expiration
2044-03-15

AI Technical Summary

Technical Problem

Existing lead-free antiferroelectric ceramics have shortcomings in energy storage efficiency and frequency stability, and it is difficult to meet the needs of high-power pulsed devices.

Method used

By multi-ion doping in relaxed ferroelectric thick film ceramics, combining wide bandgap oxides such as MgO and Ta2O5, the temperature and frequency stability of the dielectric are improved, and the casting method is used to reduce the ceramic thickness to improve the breakdown field strength.

Benefits of technology

It achieves high recoverable energy storage density (10.84J/cm3) and high energy storage efficiency (91.6%), while improving frequency and temperature stability, and is suitable for high power density pulse capacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118307319B_ABST
    Figure CN118307319B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of functional ceramics, and discloses a high energy storage lead-free relaxor ferroelectric thick film ceramic and its preparation method and application. The chemical formula of the lead-free relaxor ferroelectric thick film ceramic is (Bi 0.5‑0.5x Na 0.5‑0.5x La x )(Ti 1‑x Mg 0.66x Ta 0.33x )O3, x = 0.24. Since multi-ion doping increases the relaxation degree, the dielectric temperature and frequency stability are enhanced, and the energy storage efficiency is improved. In addition, wide bandgap oxides such as MgO (~7.7eV) and Ta2O5 (~4eV) can also increase the breakdown field strength of relaxor ferroelectric thick film ceramics. At the same time, the tape casting process is used to reduce the thickness of the ceramic and further increase the breakdown field strength. The lead-free relaxor ferroelectric thick film ceramic can be used in power pulse devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional ceramics, and more specifically, relates to a high-energy storage lead-free relaxor ferroelectric thick film ceramic and a preparation method and application thereof. Background Art

[0002] With the development of science and technology, power pulse technology has been widely used in military, medical, construction and other fields, and capacitors play an important role in power pulse devices. In order to meet the needs of various industries, the development of capacitors with high recoverable energy storage density, high energy storage efficiency and excellent working stability has become a current research hotspot. Capacitor materials are mainly divided into polymers, ceramics and composite materials. Polymer materials have a breakdown field strength far exceeding other materials, but due to their poor thermal stability and small dielectric constant, their scope of use is limited. Composite materials have some of the advantages of polymers and ceramic materials, but the current production technology is not mature and it is difficult to put into large-scale production. Although the breakdown field strength of ceramic dielectrics is not as good as the former, they have good thermal and frequency stability, and the production process is mature and stable. They are excellent dielectric choices for high-frequency pulse devices.

[0003] Relaxor ferroelectrics and antiferroelectrics are considered to be the most promising candidate materials because of their large polarization difference, recoverable energy storage density and high energy storage efficiency. Recently reported lead-free antiferroelectric ceramics include AgNbO 3 However, due to the complex manufacturing process and the use of precious metal materials such as Ag and Nb, it has poor fatigue performance, low efficiency and high cost. For example, the recoverable energy storage density of lead-free antiferroelectric ceramics prepared in patent publication number "CN116283285A" is only 6.1J / cm 3 , the energy storage efficiency is only 62%, which is difficult to meet practical applications. 3 Base ceramics, SrTiO 3 Base ceramics, Na 0.5 Bi 0.5 TiO 3 Base ceramic, K 0.5 Na 0.5 NbO 3 Base ceramics, BiFeO 3 Based ceramics have good energy storage performance and are considered to have good application prospects, while NBT-based ceramics, due to Bi 3+ 6p and O 2- The orbital hybridization of 2p electrons produces a large saturation polarization (over 40 μC / cm 2 ), so it is considered to be a better choice. Although NBT-based ceramics have a higher maximum polarization intensity (P m), but due to its low breakdown field strength, such as the NBT-based ceramics disclosed in patent publication number "CN113735578A", the breakdown field strength is only 160kV / cm, resulting in the recoverable energy storage density of only 1.1J / cm 3 Therefore, NBT-based ceramics cannot be directly used in power pulse devices. Summary of the invention

[0004] In order to solve the above-mentioned deficiencies and shortcomings of the prior art, the purpose of the present invention is to provide a lead-free relaxor ferroelectric thick film ceramic with high energy storage. The relaxor ferroelectric thick film ceramic has increased relaxation by multi-ion doping, which enhances the dielectric temperature and frequency stability, and increases the relaxation to improve the energy storage efficiency. In addition, MgO (~7.7eV) and Ta 2 O 5 Wide bandgap oxides such as (~4eV) can also increase the breakdown field strength.

[0005] Another object of the present invention is to provide a method for preparing the lead-free relaxor ferroelectric thick film ceramic. The method reduces the thickness of the ceramic sample by a tape casting method to increase the breakdown field strength. And high configuration entropy brings higher polarization strength.

[0006] Another object of the present invention is to provide an application of the above-mentioned lead-free relaxor ferroelectric thick film ceramic.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] A high energy storage lead-free relaxor ferroelectric thick film ceramic, the molecular formula of the relaxor ferroelectric thick film ceramic is (Bi 0.5-0.5x Na 0.5-0.5x La x )(Ti 1-x Mg 0.66x Ta 0.33x ) 3 , x=0.24.

[0009] Preferably, the relaxor ferroelectric thick film ceramic has a thickness of 8 to 12 μm.

[0010] The preparation method of the high energy storage lead-free relaxor ferroelectric thick film ceramic comprises the following specific steps:

[0011] S1. Na 2 CO 3 , Nb 2 O 5 、Bi 2 O 3 、TiO 2 、BaCO 3 、SrCO 3 , MgO and ZrO 2 , according to (Bi0.5-0.5x Na 0.5- 0.5x La x )(Ti 1-x Mg 0.66x Ta 0.33x ) 3 , x=0.24 in a stoichiometric ratio, and ball-milled, dried, sieved, and pre-calcined at 800-900° C. to obtain a calcined powder;

[0012] S2. The pre-fired powder was subjected to secondary ball milling, drying and sieving to obtain a dry powder, the dry powder and a dispersant, a solvent, a binder and a plasticizer were mixed and loaded into a nylon tank, and the thick film ceramic body was obtained by rolling and casting;

[0013] S3. Debinding the thick film ceramic body at 500-700° C., raising the temperature to 1000-1200° C. and sintering to obtain a lead-free relaxor ferroelectric thick film ceramic.

[0014] Preferably, the ball milling time in steps S1 and S2 is 14 to 18 hours; the sieve aperture is 80 to 200 meshes, and the pre-calcination time in step S1 is 2 to 4 hours.

[0015] Preferably, in step S2, the dispersant is toluene or fish oil; the solvent is ethanol, trichloroethylene or toluene; the binder is polyvinyl butyral (PVB) or polyvinyl alcohol (PVA); and the plasticizer is dibutyl phthalate or ethylene glycol.

[0016] Preferably, the mass ratio of the dispersant, solvent, binder and plasticizer in step S2 is 1:(0.05-0.15):1:0.1:(0.1-0.2).

[0017] Preferably, the debinding time in step S3 is 2 to 4 hours; the heating rate is 2 to 5° C. / min, and the sintering time is 3 to 5 hours.

[0018] The lead-free relaxor ferroelectric thick film ceramic is used in power pulse devices.

[0019] The lead-free antiferroelectric ceramic is used in power pulse devices.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. The multi-ion doping in the lead-free relaxor ferroelectric thick film ceramic of the present invention increases the relaxation degree and enhances the dielectric temperature and frequency stability. In addition, MgO (~7.7eV) and Ta 2 O 5Wide bandgap oxides such as (~4eV) can also improve the breakdown field strength of relaxor ferroelectric thick film ceramics. At the same time, the thickness of the ceramic is reduced by the tape casting process, which further improves the breakdown field strength. And high configuration entropy brings higher polarization strength.

[0022] 2. The lead-free relaxor ferroelectric thick film ceramic prepared by the present invention has a high recoverable energy storage density (W rec =10.84J / cm 3 ) and high energy storage efficiency (η=91.6%). Compared with other sodium bismuth titanate-based thick film ceramics, it has higher energy storage efficiency. By utilizing bandgap engineering to widen the energy band, the wide-bandgap oxides magnesium oxide and tantalum oxide are doped to make the prepared lead-free relaxor ferroelectric thick film ceramics have a wider energy band than pure sodium bismuth titanate, while reducing the grain size (1.97±0.43μm) and obtaining a higher breakdown field strength (900kV / cm). The lead-free relaxor ferroelectric ceramic can recover an energy storage density change of less than (ΔW rec ≤5%), the change in energy storage density that can be recovered at 20~150℃ is less than (ΔW rec ≤10%). It has good frequency stability and temperature stability, which is of great significance for the development of pulse capacitors with high power density and capable of coping with a variety of complex working environments.

[0023] 3. The present invention uses a sodium bismuth titanate-based ceramic system, which is more economical than most lead-free relaxor ferroelectric energy storage ceramics, does not contain lead elements, is environmentally friendly, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The dielectric temperature spectra of the relaxor ferroelectric thick film ceramic in Example 1 at different frequencies;

[0025] Figure 2 is a SEM photograph of a cross section of the relaxor ferroelectric thick film ceramic in Example 1;

[0026] Figure 3 1 is a hysteresis loop diagram of the relaxor ferroelectric thick film ceramic in Example 1;

[0027] Figure 4 Statistical diagram of energy storage density and energy storage efficiency of the relaxor ferroelectric thick film ceramic in Example 1. DETAILED DESCRIPTION

[0028] The content of the present invention is further described below in conjunction with specific examples, but it should not be construed as limiting the present invention. If not specifically indicated, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0029] Example 1

[0030] 1. Select Na with purity greater than 99% 2 CO 3 、Bi 2 O 3 、TiO 2 ,La 2 O 3 , MgO and Ta 2 O 5 As the raw material of relaxor ferroelectric thick film ceramic materials, according to (Bi 0.38 Na 0.38 La 0.24 )(Ti 0.76 Mg 0.16 Ta 0.08 ) 3 The stoichiometric ratio of the above two materials is weighed and mixed, anhydrous ethanol and zirconium balls are added, and the mixture is put into a planetary ball mill for 12 hours of mixing. The obtained slurry is filtered, dried at 105°C, and passed through an 80-mesh sieve to obtain a thick film ceramic powder. The total volume ratio of anhydrous ethanol, zirconium balls and all powders is 1:2:1.

[0031] 2. The obtained thick film ceramic powder was calcined at 850°C in a muffle furnace and kept warm for 3 hours to obtain a calcined product, and the calcined product was added with anhydrous ethanol and zirconium balls, and placed in a planetary ball mill for 12 hours of mixing. The obtained slurry was filtered and dried at 105°C and passed through a 200 mesh sieve to obtain a secondary ball-milled thick film ceramic powder. The total volume ratio of anhydrous ethanol, zirconium balls and all powders is 1:2:1.

[0032] 3. 50g of the obtained secondary ball-milled ceramic powder, 4g of toluene, 50g of ethanol, 5g of PVB, and 8g of dibutyl phthalate were placed in a nylon jar and rolled for 24h to obtain a casting slurry. The obtained casting slurry was cast on a PET film to obtain a relaxor ferroelectric thick film ceramic body.

[0033] 4. The thick film ceramic body was heated to 600℃ in a muffle furnace at a rate of 3℃ / min and kept for 3h to remove the binder, sintered at 1100℃ in an air atmosphere and kept for 4h, and cooled naturally in the furnace to obtain a relaxor ferroelectric thick film ceramic with the molecular formula (Bi 0.38 Na 0.38 La 0.24 )(Ti 0.76 Mg 0.16 Ta 0.08 ) 3 .

[0034] The sample of Example 1 was ground into powder and spread on a sample table to obtain an XRD spectrum. The XRD spectrum of the sample prepared in Example 1 was compared with the standard JCPDS card, indicating that the relaxor ferroelectric thick film ceramic prepared in the present invention has a perovskite structure without obvious secondary phase.

[0035] Figure 1 The dielectric temperature spectra of the relaxor ferroelectric thick film ceramics at different frequencies in Example 1 are shown in FIG. Figure 1 It can be seen that with the increase of frequency, the dielectric constant of the sample decreases and the dielectric peak moves toward the high temperature direction, showing the typical characteristics of relaxor ferroelectrics, namely frequency dispersion and diffuse phase transition. Figure 2 is a SEM photograph of the cross section of the relaxor ferroelectric thick film ceramic in Example 1. Figure 2 It can be seen that the grain boundaries of relaxor ferroelectric thick film ceramics are clear, the grains are dense, and there are no obvious pores. The thickness of relaxor ferroelectric thick film ceramics is measured to be 8-10μm, so a higher breakdown field strength can be obtained.

[0036] Figure 3 The hysteresis loop of the relaxor ferroelectric thick film ceramic in Example 1 is shown in Figure 1. Symmetrical gold electrodes with a diameter of 1 mm were sputtered on both sides of the sample, and high-purity silver wires were fixed on the gold electrodes using low-temperature silver paste. The single-sided PE hysteresis loop was tested using the Radiant multiferroic integrated test system. Figure 3 It can be seen that the optimal breakdown field strength of the relaxor ferroelectric thick film ceramic in Example 1 is 900 kV / cm, and the maximum polarization intensity minus the residual polarization intensity value (ΔP = P max -P r ) is 24.81μC / cm 2 , the optimal W rec The value is 10.84J / cm 3 , η value is 91.6%. According to the PE hysteresis loop, the results show that the thick film ceramic exhibits the characteristics of a typical relaxor ferroelectric, characterized by the residual polarization intensity (P r ) is reduced, the maximum polarization intensity (P max ) increases, and the hysteresis loop becomes thinner.

[0037] Figure 4 Statistical diagram of energy storage density and energy storage efficiency of the relaxor ferroelectric thick film ceramic in Example 1. Figure 4 It can be seen that the energy storage density change of the lead-free relaxor iron thick film ceramic within 1-500Hz is less than (ΔW rec ≤5%), the change in energy storage density that can be recovered at 20~150℃ is less than (ΔW rec ≤10%), with the increase of electric field strength, the recoverable energy storage density increases continuously and reaches the highest at 900kV / cm (W rec =10.84J / cm3 ), the energy storage efficiency decreases with the increase of electric field strength and reaches 91.6% at 900kV / cm, indicating that lead-free relaxor ferroelectric thick film ceramics have excellent energy storage properties, good frequency stability and temperature stability, which is of great significance for the development of pulse capacitors with high power density and capable of coping with a variety of complex working environments.

[0038] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A high energy storage lead-free relaxor ferroelectric thick film ceramic, characterized in that: The molecular formula of the relaxor ferroelectric thick film ceramic is (Bi 0.5-0.5x Na 0.5-0.5x La x )(Ti 1-x Mg 0.66x Ta 0.33x )O3, x = 0.24; the thickness of the relaxor ferroelectric thick film ceramic is 8 to 12 μm; the recoverable energy storage density of the relaxor ferroelectric thick film ceramic is 10.84 J / cm 3 , the energy storage efficiency is 91.6%; the relaxor ferroelectric thick film ceramic can recover the energy storage density change of less than 5% within 1-500Hz, and the energy storage density change of less than 10% at 20-150℃; The preparation method of the high energy storage lead-free relaxor ferroelectric thick film ceramic comprises the following specific steps: S1. Na2CO3, Bi2O3, TiO2, La2O3, MgO and Ta2O5 were mixed according to (Bi 0.5-0.5x Na 0.5-0.5x La x )(Ti 1- x Mg 0.66x Ta 0.33x )O3, x=0.24 in a stoichiometric ratio, and ball-milled, dried, sieved, and pre-calcined at 800-900° C. to obtain a calcined powder; S2. The pre-sintered powder is subjected to secondary ball milling, drying and sieving in sequence to obtain a dry powder, and the dry powder is mixed with a dispersant, a solvent, a binder and a plasticizer and loaded into a nylon can, and a thick film ceramic body is obtained by rolling and casting; the dispersant is toluene or fish oil; the solvent is ethanol, trichloroethylene or toluene; the binder is PVB or PVA; the plasticizer is dibutyl phthalate or ethylene glycol; S3. Debinding the thick film ceramic body at 500-700° C., raising the temperature to 1000-1200° C. and sintering to obtain a lead-free relaxor ferroelectric thick film ceramic.

2. The high energy storage lead-free relaxor ferroelectric thick film ceramic according to claim 1, characterized in that: The ball milling time in steps S1 and S2 is 14 to 18 hours; the sieve aperture is 80 to 200 meshes, and the pre-burning time in step S1 is 2 to 4 hours.

3. The high energy storage lead-free relaxor ferroelectric thick film ceramic according to claim 1, characterized in that: The mass of the dry powder, dispersant, solvent, binder and plasticizer in step S2 is 1:(0.05-0.15):1:0.1:(0.1-0.2).

4. The high energy storage lead-free relaxor ferroelectric thick film ceramic according to claim 1, characterized in that: The debinding time in step S3 is 2 to 4 hours; the heating rate is 2 to 5° C. / min, and the sintering time is 3 to 5 hours.

5. Use of the lead-free relaxor ferroelectric thick film ceramic according to any one of claims 1 to 4 in power pulse devices.

Citation Information

Patent Citations

  • Sodium bismuth titanate-based lead-free ferroelectric ceramic material with high dielectric temperature stability and energy storage characteristic and preparation method of sodium bismuth titanate-based lead-free ferroelectric ceramic material

    CN113735578A

  • Niobium-deficient high-energy-storage silver niobate-based lead-free antiferroelectric ceramic and preparation method thereof

    CN116283285A

  • Relaxation ferroelectric ceramic material with low electric field driving, high energy storage density and ultrafast discharge rate and preparation method thereof

    CN115108826A

  • Sodium bismuth titanate-based high-energy-storage-performance ceramic capacitor and preparation method thereof

    CN116751051A